On the assessment of the heat transfer coefficients on building components: A comparison between modeled and experimental data. (15th May 2022) - Bruno, R.; Ferraro, V.; Bevilacqua, P.; Arcuri, N.
Abstract: The thermal performances of building components require an accurate evaluation of the heat transfer processes on the internal and external surfaces. These evaluations involve the convective and the radiative heat transfer coefficients, which in actual conditions vary dynamically. Nevertheless, international standards indicate combined and steady heat transfer coefficients, especially in building energy performance calculations. In this paper, an experimental campaign carried out on a real scale measurement station available at the University of Calabria (Italy), has allowed for comparing the actual data with those calculated by a numerical code based on the Finite Difference Method (FDM), implementing the usual equations governing the heat transfer processes. The code is generalizable for every enclosure and does not require excessive computational effort. By assuming dynamic and separated heat transfer coefficients first, and successively steady and combined values, a comparison in terms of surface temperatures and transmitted thermal fluxes was conducted using the developed code on different building components, having different dispersing and thermal mass features. Regarding the measured values, the provided results showed a large discrepancy when steady and combined heat transfer coefficients are adopted, especially for the inner surfaces. Dynamic and separated heat transfer coefficients, instead, allow for meeting experimental data quite well, independently from dispersing and thermal mass characteristics. Furthermore, in simulation tools, a large discrepancy appears both in terms of energy needs and thermal comfort conditions on the experimental set-up, when simulated with steady convective heat transfer coefficients. Highlights: Experimental values were compared with modeled surface temperatures and thermal fluxes. McAdams correlations are suitable for the internal convective heat transfer coefficients. The radiance method is robust for evaluating internal radiative exchanges. Isothermal components are indicative of reliable results. Steady convective heat transfer coefficients produce in TRNSYS a worsening of the results.